Physical Equilibrium Evaluation in Parkinson Disease - Flores, Franciele da Trindade; Rossi, Angela Garcia; Schmidt, Paula da Silva (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The Parkinson disease can be among the multiple causes of alterations in the physical equilibrium. Accordingly, this study has the objective to evaluate Parkinson patients' physical equilibrium.Method: Potential study in which 12 Parkinson individuals were evaluated by way of tests of static and dynamic equilibrium, dynamic posturography and vectoelectronystagmograph. To compare the dynamic posturography results a group of gauged control was used.Results: Alterations in Romberg-Barré, Unterberger and Walk tests were found. The vestibular exam revealed 06 normal cases, 04 central vestibular syndrome and 02 cases of peripheral vestibular syndrome. In the dynamic posturography, an equilibrium alteration has been verified, when compared to the control group in all Sensorial Organization Tests, in average and in the utilization of vestibular system.Conclusion: Parkinson patients present a physical equilibrium alteration. The dynamic posturography was more sensitive to detect the equilibrium alterations than vectoelectronystagmograph.
Keywords: Parkinson disease; vestibular function test; electronystagmography